Remodeling of the Feeding Arterial System After Surgery for Resection of Brain Arteriovenous Malformations: An Observational Study. Issue 1 (12th March 2018) - Morgan, Michael Kerin; Guilfoyle, Mathew; Kirollos, Ramez; Heller, Gillian Z
Abstract: BACKGROUND: Avoiding the risk of postoperative hemorrhage after brain arteriovenous malformation (AVM) resection involves aggressive blood pressure control. Remodeling of the feeding arterial system is critical in reducing this risk. OBJECTIVE: To investigate factors predicting time to return to normal on digital subtraction angiography (DSA) after AVM resection. METHODS: For AVM in which the largest feeding artery (FA) on DSA was in the anterior circulation, the preoperative and postoperative diameter of the FA were compared with the diameter of the internal carotid artery (IC) immediately proximal to the posterior communicating artery. The preoperative FA/IC ratio (FA/IC preAVM) was compared with the first postoperative FA/IC ratio (FA/IC postAVM). Normal FA/IC ratio (FA/IC normal) was established from matched arteries in the contralateral hemisphere to the AVM. RESULTS: Eighty-six patients were analyzed for postoperative DSA performed a median 4 d after resection. From the interval-censored proportional hazards regression analysis, FA/IC preAVM (hazard ratio of 0.0006; 95% confidence interval: 0.00-0.21; P  = .013) and maximum AVM diameter (hazard ratio of 0.47; 95% confidence interval: 0.23-0.95; P  = .036) were significant in time to return to normal. These 2 factors were poorly correlated with each other (r = 0.41). AVMs with FA/IC preAVMs <0.57 combined with a diameter <3.0 cm normalize within 7 d in more than 50% of cases. Any other combination of ratio and size has fewer than 20% normalizing within 7 d (log rank P  < .001). CONCLUSION: FA/IC preAVM and AVM size are both important in predicting the time taken for return to normal feeding arterial system on DSA after AVM resection.